The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jtcme.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of curcumin on angiogenesis in a streptozotocin-induced diabetic rat model: An aortic ring assay

Abstract: BackgroundCurcumin (diferuloylmethane) has been associated with the inhibition of angiogenesis, as well as the prevention of cancers and inflammatory processes. The aim of this study was to assess the efficacy of curcumin in suppressing angiogenesis in the cultured endothelial cells of rat aortic rings.MethodsEight-week-old male Wistar rats were randomized into five groups each with a different treatment and cell culturing paradigm: controls cultured in the absence of VEGF (vascular endothelial growth factor) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“… 14 Stimulation of angiogenesis is an important aspect for normal wound healing but hyperglycemic condition in diabetic wound disrupts angiogenesis and hypoxia inducible factor (HIF) -α trans-activation 15 , 16 . The vascular endothelial growth factor (VEGF) plays an important role in signaling and balancing of neo-vascularization 17 , 18 . The VEGF signaling cascade initiated by binding with transmembrane tyrosine kinase receptors – VEGFR-I and VEGFR-II.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Stimulation of angiogenesis is an important aspect for normal wound healing but hyperglycemic condition in diabetic wound disrupts angiogenesis and hypoxia inducible factor (HIF) -α trans-activation 15 , 16 . The vascular endothelial growth factor (VEGF) plays an important role in signaling and balancing of neo-vascularization 17 , 18 . The VEGF signaling cascade initiated by binding with transmembrane tyrosine kinase receptors – VEGFR-I and VEGFR-II.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also found that curcumin attenuates high glucose-induced neonatal rat cardiomyocyte apoptosis by inhibiting NADPH oxidasemediated oxidative stress and this protective effect is most likely mediated by PI3K/Akt-related signaling pathway [61]. A recent study showed that curcumin inhibits angiogenesis in a STZ-induced diabetic rat model with an aortic ring assay [62]. Curcumin also offers a protective effect against various organs and tissue damage that could occur either directly or indirectly as a result of the persistence of hyperglycemia.…”
Section: Curcuminmentioning
confidence: 99%
“…Irregularities in the aortic segments have been identified as one of the drawbacks of this assay (Staton et al, ). To evaluate the effects of curcumin on angiogenesis, the aortic ring assay has been included in a study carried out by Dehghan et al (). Ben‐Mabrouk et al () have also used the aortic ring assay to report in vitro anti‐angiogenic effects of CC5 and CC8, disintegrins isolated from the venom of Cerastes cerastes viper.…”
Section: Assays and Techniques Used To Monitor Angiogenesismentioning
confidence: 99%